2017
DOI: 10.14214/sf.7721
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral UAV-imagery and photogrammetric canopy height model in estimating forest stand variables

Abstract: Hakala T., Viljanen N. (2017). Hyperspectral UAV-imagery and photogrammetric canopy height model in estimating forest stand variables. Silva Fennica vol. 51 no. 5 article id 7721. 21 p. https://doi.org/10.14214/sf.7721 Highlights• Hyperspectral imagery and photogrammetric 3D point cloud based on RGB imagery were acquired under weather conditions changing from cloudy to sunny.• Calibration of hyperspectral imagery was required for compensating the effect of varying weather conditions. • The combination of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…The method was developed in a previous study [12,32], and it has been used to correct datasets captured in various environmental remote sensing applications [12,[33][34][35][36]. In this study, we implemented and assessed the combined adjustment model including the absolute calibration using reflectance panels and option to process images captured with different solar elevations simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The method was developed in a previous study [12,32], and it has been used to correct datasets captured in various environmental remote sensing applications [12,[33][34][35][36]. In this study, we implemented and assessed the combined adjustment model including the absolute calibration using reflectance panels and option to process images captured with different solar elevations simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The image-wise relative correction parameters (a rel ) have been significant in the studies carried out under varying weather conditions [12,[34][35][36], while when capturing images in sunny conditions, the BRDF corrections have been significant [12,33]. The importance of utilizing the onboard irradiance recordings were shown in particular in the investigation concerning tree species classification and estimating forest stand variables, where the datasets were captured over a test area covering over 10 km during two days under highly variable weather conditions [35,36]. Comparisons of analysis with and without radiometric correction have shown that the radiometric correction improved the estimation results [12,36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations